Antipredator responses toward cat fur in wild brown rats tested in a semi-natural environment. (26th May 2021) - Bedoya-Pérez, Miguel A; Le, Anna; McGregor, Iain S; Crowther, Mathew S
Abstract: Sensitivity to predator-related cues and performance of antipredator behaviors are universal among prey species. Rodents exhibit a diverse suite of antipredator behaviors that have been examined in both field and laboratory studies. However, the results from the laboratory have not always translated to the field. While laboratory studies consistently indicate strong fear-inducing effects of cat fur/skin odors, it is unclear whether this occurs in the field with wild rats. To address this issue, we tested the antipredator responses of wild brown rats ( Rattus norvegicus) to predatory (domestic cat fur) and nonpredatory (common brushtail possum fur) odor cues in a semi-natural experimental paradigm. Rats were housed in open air enclosures containing two feeding stations. Following several nights of acclimatization, the feeding stations were paired with cat fur, possum fur, or no fur. Rats spent less time at a feeding station that was paired with cat fur. Duration of time spent at feeding stations increased across consecutive test days and across hours within individual test nights, although the rate of increase within nights was lower for cat fur paired stations. This overall increase might reflect habituation of antipredator behaviors, increasing hunger, or loss of cue potency over time. We suggest that wild brown rats recognize and respond to cat fur odor cues, but their behavioral response is highly adaptable and finely tuned to the trade-off between predation risk and starvation that occurs across short temporal scales. Abstract : Driven by the constant trade-off between starvation and predation risk, prey species have evolved sensitivity to predator cues coupled to a suite of antipredator behaviors. There are, however, some inconsistencies between the results of field and laboratory research around responsiveness to predator odors. In the current study, we examine the avoidance response of captive wild rats toward cat fur in a semi-natural environment. Wild rodents were sensitive to this cue particularly when tested in a choice paradigm involving high cost-benefit trade-off.